Attenuation of River Contaminant using River Bank Infiltration in Jenderam Hilir, Dengkil, Selangor - Shamsuddin, Mohd Khairul Nizar; Suratman, Saim; Tajul Baharuddin, Mohd Faizal (International Journal of Integrated Engineering, 2013)
Bank infiltration (BI) refers to the process of surface water seeping from the bank or bed of a river to the groundwater production wells. During the water’s passage through the ground, its quality changes due to microbial, chemical and physical processes, and due to mixing with groundwater in the aquifer. The BI study in Jenderam Hilir, Selangor is a pilot project to develop a better and sustainable source of water, and will provide a good platform to introduce this method in Malaysia. BI has been successfully implemented in many Asian and European countries. This site was chosen due to the high water demand in the area and groundwater is seen as one of the source with very high potential to be developed as supplementary source to meet the high public water supply demand. The objective of this study is to determine the effectiveness of BI and improving the quality of river water, and to determine the effective rate of water extraction from the alluvium in the study area. Twenty five (25) monitoring wells and 2 test wells were constructed at the study site and pumping tests have been carried on these two test wells. The pumping tests at the 2 test wells indicated that DW1 and DW2 were able to produce more than 15.9 m3/hr (0.3816 MLD) and 128m3/hr (3.072 MLD) respectively during the duration of 72 hours pumping tests with drawdown for DW1 was 4.17 m and DW2 was 2.63 m. The distance between the river and the test well is more than 18 m and the shortest travel time is 10 days. The river water was filtered through a 16 m thick silty sand for DW1 and 13 m thick gravelly sand for DW2. Both wells are located in confined aquifer adjacent to the Sungai Langat. Water quality analyses carried out for water from the Sungai Langat and groundwater from the wells showed decreased in turbidity, nitrate, aluminium and sulphate in groundwater which were very high in the Sungai Langat. Microorganism counting (E. coli, total coliform, Cryptosporidium and Giardia) was also carried out. Results of sampling from the 2 test wells confirmed that the microorganism counts were significantly reduced during the passage in BI which is capable to achieve more than 99.9 % removal of E. coli, total coliform and Giardia. The study on the effectiveness of BI method is a proactive effort of NAHRIM to improve surface water quality as a source for domestic water of the modern urbanised area.